The Integration of Intensive Standard Milk Production Systems in the Jura Mountain Region by PDO Cheese Chains - Philippe Jeanneaux (Revue de Géographie Alpine)
Despite the hegemony of the Jura dairy production system based on PDO cheeses, in the 1970s the Jura Mountain was involved in the gradual construction of an intensive agri-industrial sector. However, this intensive agri-industrial sector has always been hidden by the PDO Comté value chain. The aim of this article is to understand this little-known, intensive and standardized Jura dairy sector and analyse its contemporary dynamic. To address this objective, we processed data from the annual dairy survey carried out by DRAAF BFC, and updated research made in the 1990s to understand the strategies of cheese processors. We interviewed stakeholders who have been in business for the past 30 years. We also used various administrative, legal and academic sources. Our results show that this intensive dairy region was never really “territorialized”. Indeed, although it was centred on the Doubs plain and the first plateau, it could move up to the second plateau, while Comté cheese dairies (fruitières) were to be found on the plain. In other words, the two systems overlapped. We show a process of integration of this standard milk industry by a powerful localized PDO cheese production system. Rather than the intensive dairy industry fading away in the face of PDO cheeses, we’re in a situation where the success of the PDO sector has strongly stimulated the agri-industrial sector and enforced dairy processors to reinvent themselves by adopting the production of PDO cheeses or cheeses with a “terroir” image (raclette, for example). This stimulating competition within the Jura dairy sector has made it one of France’s few growing dairy regions. This case is interesting because it also suggests that the artisanal model of the “fruitière” has more than held its own against competition from the big dairy companies.